How can pluralistic organizations proceed with strategic change? A processual account of rhetorical contestation, convergence, and partial agreement in a Nordic city organization - Sorsa, V; Vaara, E (INFORMS, 2020)
This study examines how pluralistic organizations confronting fundamental differences in values can proceed with strategic change. By drawing on a longitudinal case analysis of strategic change in a Nordic city organization, we show how the proponents and challengers play a “rhetorical game” in which they simultaneously promote their own value-based interests and ideas and seek ways to enable change. In particular, we identify a pattern in which the discussion moved from initial contestation through gradual convergence to increasing agreement. In addition, we elaborate on four rhetorical practices used in this rhetorical game: voicing own arguments, appropriation of others’ arguments, consensus argumentation, and collective we argumentation. By so doing, our study contributes to research on strategic change in pluralistic organizations by offering a nuanced account of the use of rhetoric when moving from contestation to convergence and partial agreement. Furthermore, by detailing specific types of rhetorical practices that play a crucial role in strategy making, our study advances research on the role of rhetoric in strategy process and practice research more generally.